2017
DOI: 10.1063/1.4993200
|View full text |Cite
|
Sign up to set email alerts
|

Study of fractal features of magnetized plasma through an MHD shell model

Abstract: A magnetohydrodynamic (MHD) shell model is used to describe the dissipative events which take place in magnetized plasmas. A scatter plot box-counting fractal dimension D is calculated for the time series of the magnetic energy dissipation rate obtained in the MHD shell model, and the correlation between D and the energy dissipation rate is analyzed. We show that, depending on the values of the viscosity and the diffusivity, the fractal dimension and the occurrence of bursts exhibit correlations similar to tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…Compare, for instance, the different panels in Fig. 16 in Domínguez et al (2017), which show that Pm = 0.2 leads to a very noisy output, unlike simulations with Pm = 1.0 or 2.0, where individual, large peaks can be easily identified from the background. In fact, previous studies have shown that the statistics of bursts follows a power law for Pm = 1 (Boffetta et al, 1999;Lepreti et al, 2004;Carbone et al, 2002), and for this reason we start by taking Pm = ν/η = 1.…”
Section: Mhd Shell Modelmentioning
confidence: 92%
See 4 more Smart Citations
“…Compare, for instance, the different panels in Fig. 16 in Domínguez et al (2017), which show that Pm = 0.2 leads to a very noisy output, unlike simulations with Pm = 1.0 or 2.0, where individual, large peaks can be easily identified from the background. In fact, previous studies have shown that the statistics of bursts follows a power law for Pm = 1 (Boffetta et al, 1999;Lepreti et al, 2004;Carbone et al, 2002), and for this reason we start by taking Pm = ν/η = 1.…”
Section: Mhd Shell Modelmentioning
confidence: 92%
“…In a previous work (Domínguez et al, 2017), we have applied the box-counting fractal dimension to study the complexity in an MHD shell model, analyzing the correlation between it and the energy dissipation rate, showing that, for certain values of the viscosity and the magnetic diffusivity, the fractal dimension exhibits correlation with the occurrence of bursts, similar to what had been found with geomagnetic data (Domínguez et al, 2014). This suggests that shell models do not only reproduce the power-law statistics of dissipative events in turbulent plasmas but also some features of its fractal behavior.…”
mentioning
confidence: 90%
See 3 more Smart Citations